(untitled) (The Research of Medical Science Review, 2025)
Retinopathy of premature infants also termed as retrolental fibroplasia, is a vascular proliferation retinopathy which forms due to vascular proliferation in a retina that has not completed its vascularization, leading to different outcomes, which vary from normal vision to blindness. Objective: To compare the effects of invasive and non-invasive mechanical ventilation on the incidence and severity of Retinopathy of Prematurity (ROP) in premature infants. Methods: This Descriptive case series study conducted at the Department of Pediatrics Medicine, Sir Ganga Ram Hospital, Lahore, over a six-month period. A total of 137 premature infants were included, selected through non-probability consecutive sampling. Results: ROP was observed in 30.7% of the infants, with a significantly higher incidence in the invasive group (71.4%) compared to the non-invasive group (28.6%) (p = 0.001). Severe ROP was more prevalent in the invasive group (40%) than the non-invasive group (16.7%) (p = 0.04). Lower gestational age (<28 weeks) and birth weight (<1.0 kg) were strongly associated with higher ROP incidence (p < 0.05). Conclusion: It is concluded that non-invasive mechanical ventilation is associated with a lower incidence and severity of ROP compared to invasive ventilation. Gestational age and birth weight are critical risk factors. Non-invasive methods and targeted monitoring can help reduce ROP burden and improve neonatal outcomes.